Effects of sport and physical recreation on health-related outcomes among children and young people with physical disability: systematic review with meta-analysis - Catherine Sherrington; Juliana S Oliveira; Leanne Hassett; Stephen Gilbert; Amabile B Dario; Kerry West; Jennifer N Baldwin; Heidi Gilchrist; Minke Geerts; Wing S S Kwok; Rae Anderson; Gavin John Robertson (BMJ Open Sport & Exercise Medicine)
Objectives To describe quantitative studies of sport or physical recreation for children and young people with physical disability and evaluate effects on health-related outcomes.Design Systematic review with meta-analysis of randomised controlled trials.Data sources Six databases searched from inception to December 2023.Eligibility criteria Quantitative studies evaluating sports or physical recreation among children and young people≤18 years with physical disability.Results 77 studies (n=2584) were included in the review, with 11 randomised controlled trials included in meta-analyses. Pre–post measurement design, health condition cerebral palsy and intervention of dance were most common. Meta-analysis could not be performed for participation outcomes because there were only two eligible trials. Sport and physical recreation had a small positive impact on activity limitations (nine trials, n=271, standardised mean difference (SMD) 0.30, 95% CI 0.02 to 0.57, p=0.018, low certainty evidence) and a medium positive impact on physical impairment (seven trials, n=216, SMD 0.63, 95% CI 0.08 to 1.18, p=0.025, very low certainty evidence) compared with control. No effect was found on quality of life (three trials, n=133, SMD −0.02, 95% CI −0.42 to 0.38, p=0.917, moderate certainty evidence) or cognitive or behavioural impairment (four trials, n=124, SMD 0.54, 95% CI −0.29 to 1.36, p=0.202, very low certainty evidence). A small number of mild adverse events were reported.Conclusion Sport and physical recreation likely improve activity and physical impairment outcomes for children and young people with physical disability. More research assessing participation outcomes and evaluation of existing sport and recreation programmes in the community is indicated.PROSPERO Registration Number CRD42020159283